Efeito de parâmetros analíticos sobre a precisão de métodos de extração de zinco do solo - Pessôa Da Cruz, Mara Cristina [UNESP]; Fessel Graner, Celso Augusto [UNESP]; Ferreira, Manoel Evaristo [UNESP] (My University, 1997)
Fifteen soil samples and four extradants (DTPA, Na 2EDTA, HCl and Mehlich 1) were used to study soil extraction methods for available zinc. Each extradant was studied in three soil:solution ratios (1:2, 1:4 and 1:10) and in three extraction periods in the ratio most frequently used. The zinc extracted by DTPA, Na 2EDTA and HCl was not affected by use of soil:solution ratios 1:2 and 1:4, but the amount extracted increased with the 1:10 ratio. In this relation, the variation coefficients increased. With Mehlich, no definite tendency was observed. The increase of extraction period for DTPA extractant, in 1:2 ratio, had little effect on the amount of zinc extracted and on the precision. As to Na 2EDTA extractant in 1:10 ratio, with the increase of extraction time, both increased. As to HCl and Mehlich, both in 1:4 ratio, the increase in extraction period had no effect on the amount of zinc extracted and no definite effect on the precision. Thus, the use of 1:2 ratio for DTPA and Na 2EDTA and 1:4 ratio for acid extractants is recommended. Concerning the period of extraction, 120 min should be used with DTPA and Na 2EDTA, 15 min with HCl and 5 min with Mehlich.

Amostras de quinze solos representativos do Estado de São Paulo e quatro extratores (DTPA, Na2EDTA, HCl, e Mehlich 1) foram usados em estudo de métodos de extração de zinco do solo. Cada extrator foi estudado nas relações solo: solução extratora de 1:2, 1:4 e 1:10 e em três tempos de agitação na relação mais comumente adotada em cada caso. Com os extratores DTPA, Na2EDTA e HCl, a quantidade extraída de zinco se manteve praticamente inalterada nas relações solo: solução de 1:2 e 1:4, e aumentou na relação 1:10, a qual resultou em coeficientes de variação maiores. Com o Mehlich, não houve tendência definida. O aumento do tempo de agitação com o DTPA, na relação 1:2, praticamente não afetou a quantidade extraída, nem a precisão. Com o Na2EDTA, na relação 1:10, ambas aumentaram. Com o HCl e o Mehlich, ambos na relação 1:4, o aumento do tempo de agitação não afetou a quantidade extraída, e não teve efeito definido sobre a precisão. Assim, recomenda-se o emprego da relação 1:2 com os extratores complexantes, e 1:4, com os ácidos. Quanto aos tempos de agitação, recomenda-se 120 min com os complexantes, 15 min com o HCl e 5 min com o Mehlich.
Effect of analytical parameters on the precision of soil zinc extraction methods
Keywords: DTPA; HCl; Mehlich 1; Micronutrient; Na 2EDTA; Soil fertility evaluation; Soil test